KONSEP AL-NAFS DALAM KAJIAN TASAWUF AL-GHAZá¾¹LÄª - Paisol Burlian, Paisol (TEOLOGIA, 2013)
Abstract: This article will elaborate on al-nafs (soul) which is an essential part of human nature. The Sufis divide understanding al-nafs in three senses. First, al-nafs is a substance that distinguishes human qualities with other creatures. Second, al-nafs is the cause of man to be creative and dynamic, through the process of inspiration and contemplation. Therefore, the level of quality of the nafs is different. In the literature of Sufism, the nafs can be transformed from a trend that is closest to the bad action to the level of closeness to the divine tenderness. Third, the nafs is the impulse of anger and lust, and urge all reprehensible nature, and immoral in mind. Sufi Sunni, al-GhazÄlÄ« calls nafs as the center of the potential upset, and the base of the despicable nature. Therefore, al-nafs need to be purified so that the properties of self perverted man disappeared. Road purification al-nafs is riyÄá¸ah and mujahadah who constantly so al-nafs is ultimately up to the level of the nafs al-muá¹mainnah. Abstrak: Artikel ini akan mengelaborasi tentang al-nafs (jiwa) yang merupakan bagian yang penting dari hakikat manusia. Para sufi membagi pengertian al-nafs ini dalam tiga pengertian. Pertama, al-nafs merupakan substansi yang membedakan kualitas manusia dengan makhluk yang lain. Kedua, al-nafs merupakan penyebab manusia menjadi kreatif dan dinamik, melalui proses inspirasi dan tafakur. Karena itu, tingkatan kualitas nafs orang berbeda-beda. Dalam literatur tasawuf, nafs ini dapat ditransformasikan dari kecenderungan yang paling dekat pada tindakan buruk sampai ke tingkat kedekatan pada kelembutan ilahi. Ketiga, nafs ialah dorongan amarah danÂ  syahwat, serta dorongan segala sifat tercela, dan maksiat dalam batin. Seorang sufi Sunni, al-GhazÄlÄ« menyebut nafs sebagai pusat potensi marah, dan pangkal dari sifat tercela. Karena itu, al-nafs ini perlu disucikan agar sifat-sifat tercela itu lenyap dari diri manusia. Jalan penyucian al-nafs adalah riyÄá¸ah dan mujÄhadah yang terus-menerus sehingga al-nafs pada akhirnya sampai pada tingkat nafs al-muá¹mainnah. Keywords: al Nafs, laá¹Ä«fah al-rabbÄniyah, sufi, al-Quran, dan al-Sunnah.